Nexus Ecotheology Curriculum Standards Policy: A Strategic Solution to Overcome Epistemological Fragmentation of Education at IAIN Pontianak - Noviansyah (JURNAL ILMIAH GEMA PERENCANA, 2026)
West Kalimantan, as the epicenter of the world's lungs, continues to face the threat of massive environmental degradation, yet Islamic education at IAIN Pontianak remains trapped in a textual-sky paradigm that is sterile from ecological issues. The focus of this study is to formulate a curriculum reorientation through the Ecotheological Nexus standards to address epistemological fragmentation. The main gap is found in the sharp separation between theological doctrine and natural responsibility, where the curriculum exists dichotomously and anthropocentrically. Specific issues examined include the dominance of sectoral egos of scientific disciplines and the absence of integrative instruments in the curriculum, courses, and Semester Learning Plans (RPS). This study is urgent to maintain the institution's relevance amidst the global climate crisis. Using a descriptive qualitative approach with a case study design, this policy study makes IAIN Pontianak's curriculum documents the primary object of study through document analysis instruments. The results show that scientific fragmentation causes students to experience "ecological blindness" despite having a strong normative understanding. The main findings emphasize that integration can only occur through mandated regulatory intervention. In conclusion, the lack of operational standards is a major obstacle to the unification of science and religion. The strategic recommendation addressed to policy makers is to immediately ratify the Chancellor's Decree on the Nexus Ecotheology Curriculum Standards as a mandatory legal umbrella for integrating environmental issues across all study programs substantially.